Sexual dysfunction following low-dose-rate brachytherapy for prostate cancer - A. D. Anosov; M. E. Efremov; V. L. Medvedev; M. I. Kogan (Вестник урологии)
Prostate cancer (PCa) is one of the most prevalent forms of male malignancies globally, ranking second in terms of incidence and sixth in terms of mortality. Low-dose-rate brachytherapy (LDRT) represents a treatment modality for PCa, involving the implantation of permanent radioactive sources into the prostate tissue. The isotopes predominantly utilised are I–125 and Pd–103. LDRT demonstrates high rates of biochemical and clinical relapse-free survival, with cancer-specific and overall survival rates comparable to those achieved through radical prostatectomy. Despite the advantages associated with LDRT, evidence has accumulated regarding the potential complications accompanying this treatment approach, including sexual dysfunction and erectile dysfunction. Sexual satisfaction constitutes a critical concern for men undergoing PCa treatment. It is essential that both the patient and the healthcare provider prioritise not only erectile function but also the preservation of sexuality in its entirety.   The present study endeavours to evaluate the accumulated material on the topic of diagnosing and treating sexual dysfunctions following low-dose-rate brachytherapy (LDRT).   The analysis encompassed articles by foreign and domestic authors published between 2014 and 2024, as well as fundamental articles and literature dating back earlier. These works were devoted to sexual dysfunction, assessment, and rehabilitation of sexual function in patients with PCa who underwent LDRT. Our review confirmed the existing necessity for a detailed study of rational methods for diagnosing sexual dysfunctions prior to selecting a treatment method, as well as the possible prevention of disorders after LDRT. It is also essential to develop sexual and penile rehabilitation strategies following LDRT for PCa, which is currently widely employed.